2022
DOI: 10.1155/2022/7247932
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Role of Medical IoT‐Based Bone Age Determination in the Diagnosis and Clinical Treatment of Dwarfism Disease Monitoring

Abstract: Currently, the prevalence of dwarfism in children in China is about 3%, which is a very large percentage compared with the large population base. With the increase of influencing factors, the prevalence of dwarfism is on the increase. However, there is a lack of awareness of dwarfism among parents and a lack of in-depth analysis of the causes of dwarfism and a low level of treatment among doctors. Early expert system knowledge base relies on manual editing, which is a traditional, semi-intelligent auxiliary di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%